2015
DOI: 10.3109/19396368.2015.1020116
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypomethylation predisposes sperm to DNA damage in individuals with varicocele

Abstract: This study aimed to assess and compare global DNA methylation (GDM) between fertile men and infertile men with varicocele. In addition, we evaluated the correlations between DNA methylation with reactive oxygen species (ROS), protamine deficiency, and DNA integrity. Semen samples were collected from 44 men with grades II and III varicocele, and 15 fertile men for assessment of semen parameters, DNA methylation, DNA fragmentation, oxidative stress, and protamine deficiency. Samples were evaluated by the World H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 36 publications
10
40
0
Order By: Relevance
“…In this study, patients with varicocele had significantly low sperm and total sperm counts, compared with nonvaricocele subjects. These results are consistent with previous studies, which reported abnormalities in the semen parameters of varicocele patients (19)(20)(21). Our findings also revealed that a higher grade of varicocele is associated with reduced sperm count and volume; the G3 group had a lower sperm and semen volume, compared to other groups.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, patients with varicocele had significantly low sperm and total sperm counts, compared with nonvaricocele subjects. These results are consistent with previous studies, which reported abnormalities in the semen parameters of varicocele patients (19)(20)(21). Our findings also revealed that a higher grade of varicocele is associated with reduced sperm count and volume; the G3 group had a lower sperm and semen volume, compared to other groups.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies demonstrated that heat-related oxidative stress or protamine deficiency in varicocele condition prone spermatozoa to DNA fragmentation (Bahreinian et al, 2015;Ni et al, 2016). In this study, we observed a significant reduction in percentage of residual histone in varicocelized rats that received Vit B+Vit E compared with varicocelized rats that received water at 4 months.…”
Section: As Shown Insupporting
confidence: 57%
“…Finally, we have previously shown in humans that varicocoele induces a state of DNA hypo-methylation that predisposes to DNA damage [12] and that is overcome by varicocoelectomy [13]. Singh et al [14] explain how the one-carbon cycle provides activated methyl groups necessary for the methylation of DNA and proteins, affecting both gene expression and protein function.…”
Section: Discussionmentioning
confidence: 99%